What motivates WA public to give money to not-for-profit organisations - Oroz, Ivana; Shanka, Tekle; Handley, Brian (University of Western Sydney, 2008)
This paper presents the results of a survey conducted on the giving behaviour among Western Australians (WA) using Sargeant et al (2006) instrument. A convenience sample of 400 members of the general public in WA voluntarily participated in an intercept survey to explore motivations behind giving money to and not for profit organisations. Results highlighted trust as a significant predictor of giving behaviour intentions. Trust and commitment were showed statistically significant differences among the various age groups whereas communication, family, and guilt components highlighted significant differences on gender. Results are discussed and further research directions are suggested.